ADS 201 Additional Help- Whole-of-Project Evaluation - USAID (USAID, 2017)

Connecting the Dots: Systems Practice & Political Economy Analysis - Walker, Tjip; Jacobstein, David (Local Systems Community, 2017)
This slide deck, from a presentation to the Local Systems Community by Tjip Walker and David Jacobstein, shows various ways in which assessing the political economy of a context and understanding that context through the lens of systems thinking can reinforce each other. Effective systems practice should be grounded in the incentives and power dynamics of a particular local system; thinking and working politically requires understanding the systems dynamics of an issue or sector.

USAID ADS 201 - Program Cycle Operational Policy (Update 1/23/2017) - USAID (USAID, 2017)
The Program Cycle is USAID’s operational model for planning, delivering, assessing, and adapting development programming in a given region or country to advance U.S. foreign policy. It encompasses guidance and procedures for: 1) Making strategic decisions at the regional or country level about programmatic areas of focus and associated resources; 2) Designing projects and supportive activities to implement strategic plans; and 3) Learning from performance monitoring, evaluations, and other relevant sources of information to make course corrections as needed and inform future programming.